Pengaruh Relaksasi Autogenik Terhadap Penurunan Tekanan Darah Pada Pasien Hipertensi Di RSU Kab Tangerang - Marlin Brigita L.; Suhaebah Wulansari (Jurnal Kesehatan, 2022)
Hypertension is a major cause of death due to stroke and a factor that can aggravate Myocardial Infarction (heart attack). Purpose of this study was to determine the effect of autogenic relaxation on reducing blood pressure. Research Methodology The design in this study was quantitative with a quasi- experimental design. This type of research uses a pre and post test control group design approach. The sample in this study used simple random sampling. The number of respondents 30 people were divided into two groups, namely 15 respondents in the intervention group and 15 respondents in the control group, then for the intervention group, autogenic relaxation was performed three times and blood pressure was measured twice. In the control group only blood pressure was measured the same as the intervention group. Results of the statistical test used by the Mann Whitney U showed that there was an effect of autogenic relaxation on decreasing blood pressure in systolic blood pressure (P=0.016) and diastolic blood pressure (P=0.033) with P value <0.05. It was concluded in this study, there is an effect of autogenic relaxation on reducing blood pressure with hypertension.